Insect meals in fish nutrition - Silvia Nogales‐Mérida; Paola Gobbi; Damian Józefiak; Jan Mazurkiewicz; Krzysztof Dudek; Mateusz Rawski; Bartosz Kierończyk; Agata Józefiak (Reviews in Aquaculture, 2019)
Different studies have shown that insect meals can partially or completely replace the fish and soya bean meals that are commonly used in aquaculture. However, information is lacking on the amino acid and fatty acid contents and digestibility of different insect meals. Moreover, we evaluated different proportions of insect diets and determined how these affected the nutritional values of insect meals. Our purpose was to clarify these aspects and consider the availability of protein, amino acids, lipids and fatty acids in insect meals in fish nutrition. Generally, insect meals have higher indispensable amino acid contents than other meal types, with contents closely related to those in fish meal. Insect meal can be an important source of essential amino acids such as methionine, with contents ranging between 0.47 and 4.03 g 100 g −1 sample. These values are higher than those reported for other animal and plant meals. In addition, insects are also good sources of lipids and fatty acids, and the amounts and types of fatty acids vary according to the species, stage of development and type of feed. Moreover, the additional nutritional value of insect meal includes compounds such as chitin, which is primarily considered a fibre but also contains nitrogen and amino acids. Insect peptides with activity against pathogenic microflora provide secondary biological effects, which may significantly improve animal health.